2011
DOI: 10.1182/blood.v118.21.1092.1092
|View full text |Cite
|
Sign up to set email alerts
|

Does Quantitative Heterogeneity of Human Fetal Hemoglobin (Hb F) Reveal Friends or Foes of KLF1 in Globin Gene Switching ?

Abstract: 1092 The chemical heterogeneity of fetal hemoglobin (Hb F) due to variable ratios of the Gγ and Aγ globin subunits reflects genetic complexity because of common dimorphisms such as Hb F Sardegna (or Aγ75(E19) Ile>Thr; also known as AγT) in Caucasians, and common variants such the Gγ globin variant, Hb F Malta I (or Gγ117(G19) His>Arg) that is in tight linkage disequilibrium with the β globin variant Hb Valletta (or β87(F3) Thr>Pro) and is found in 1.8% of neonates from Malta. Comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This discrepancy may be explained by the presence of other HbF‐modifying gene alleles in this particular Maltese family. Indeed, the same laboratory has recently reported that such elevated levels of HbF were not found in a second Maltese family carrying the same KLF1 mutation [Felice et al, ], confirming that KLF1 haploinsufficiency was not directly responsible for the very high levels of HbF observed in the first Maltese family. In summary, although our data corroborate the statement of Borg and colleagues that KLF1 haploinsufficiency causes HPFH, they also indicate that KLF1 haploinsufficiency can not alone account for levels of HbF > 5% in adults.…”
Section: Discussionmentioning
confidence: 76%
“…This discrepancy may be explained by the presence of other HbF‐modifying gene alleles in this particular Maltese family. Indeed, the same laboratory has recently reported that such elevated levels of HbF were not found in a second Maltese family carrying the same KLF1 mutation [Felice et al, ], confirming that KLF1 haploinsufficiency was not directly responsible for the very high levels of HbF observed in the first Maltese family. In summary, although our data corroborate the statement of Borg and colleagues that KLF1 haploinsufficiency causes HPFH, they also indicate that KLF1 haploinsufficiency can not alone account for levels of HbF > 5% in adults.…”
Section: Discussionmentioning
confidence: 76%